2017
DOI: 10.1186/s12917-017-1159-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary bacterial organic selenium on growth performance, antioxidant capacity, and Selenoproteins gene expression in broiler chickens

Abstract: BackgroundSelenium (Se) is an essential trace mineral in broilers, which has several important roles in biological processes. Organic forms of Se are more efficient than inorganic forms and can be produced biologically via Se microbial reduction. Hence, the possibility of using Se-enriched bacteria as feed supplement may provide an interesting source of organic Se, and benefit broiler antioxidant system and other biological processes. The objective of this study was to examine the impacts of inorganic Se and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 48 publications
(53 reference statements)
8
47
0
2
Order By: Relevance
“…Regarding selenium supplementation, there were non-significant differences between selenium treatment and control for urea, creatinine, ALT and AST. These results agree with the results of Gružauskas et al (2013), Okunlola et al (2015) and Dalia et al (2017) who indicated that there were no differences in urea and creatinine in poultry supplemented with organic or inorganic selenium. At the opposite way, Perić et al (2009), Biswas et al (2011) and Dalia et al (2017) showed that Se supplementation as inorganic or organic forms significantly decreased (P < 0.05) the activities of AST , ALT enzymes and creatinine level in birds fed selenium compared to basal diet.…”
Section: Blood Biochemical Profilessupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding selenium supplementation, there were non-significant differences between selenium treatment and control for urea, creatinine, ALT and AST. These results agree with the results of Gružauskas et al (2013), Okunlola et al (2015) and Dalia et al (2017) who indicated that there were no differences in urea and creatinine in poultry supplemented with organic or inorganic selenium. At the opposite way, Perić et al (2009), Biswas et al (2011) and Dalia et al (2017) showed that Se supplementation as inorganic or organic forms significantly decreased (P < 0.05) the activities of AST , ALT enzymes and creatinine level in birds fed selenium compared to basal diet.…”
Section: Blood Biochemical Profilessupporting
confidence: 92%
“…Regarding selenium addition, the results agree with Yang et al (2012) and Dalia et al (2017) who demonstrated that supplementation of inorganic or bacterial organic selenium did not affect total protein, albumin, globulin, albumin/globulin ratio in broiler chicks. Contrary to our findings, Mohapatra et al (2014) stated that supplementation of 0.3 ppm nano Se in layer chicks up to 8 weeks significantly increased total protein and serum globulin levels and also significantly lowered albumin/globulin ratio compared to control treatment.…”
Section: Blood Biochemical Profilessupporting
confidence: 90%
See 1 more Smart Citation
“…The form of dietary Se supplementation for the domestic animals is object of study for several species, since different authors verified higher bioavailability of organic sources compared to the commonly used inorganic source (Bertechini et al, ; Calvo, Toldrá, Rodríguez, Lópes‐Bote, & Rey, ; Cao, Fucun, Liying, Bing, & Limin, ; Dalia, Loh, Sazili, Jahromi, & Samsudin, ; Lisiak et al, ; Silva et al, ). Due to the higher bioavailability and higher muscle retention, the organic sources provide better pig meat quality results, including reduced exudation losses, lower cooking loss (CL) and lower lipid peroxidation index, indicating a longer shelf life of these meats (Bobcek et al, ; Calvo et al, ; Kim & Mahan, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that dietary Se increased the Se concentrations in the liver, kidney and muscle of broilers, while Se yeast (SY) produced higher concentrations than SS [ 9 , 10 ]. Dalia et al [ 11 ] also reported that broiler chickens receiving bacterial organic Se had higher tissue Se deposition and better antioxidant status [ 11 ]. What’s more, Se accumulation and GPx activity of broiler breeders were higher in the group fed 0.30 mg/kg SY compared to 0.30 mg/kg of SS [ 12 ].…”
Section: Introductionmentioning
confidence: 99%